The Determination of Natural Frequencies of Rectangular Plates with Mixed Boundary Conditions by Discrete Singular Convolution - WEI, G. W. (Institutional Knowledge at Singapore Management University, 2001)
This paper introduces the discrete singular convolution algorithm for vibration analysis of rectangular plates with mixed boundary conditions. A unified scheme is proposed for the treatment of simply supported, clamped and transversely supported (with nonuniform elastic rotational restraint) boundary conditions. The robustness and reliability of the present approach are tested by a number of numerical experiments. All results agree well with those in the literature.